Tungsten inert gas surface alloying of commercial purity titanium (CP-Ti) with Fe-C-Si ternary mixtures - Adeleke, S.A.; Maleque, Md. Abdul (Trans Tech Publications, Switzerland, 2014)
In the present study, the surface of commercial purity titanium (CP-Ti) was alloyed with preplaced powder of Fe, C and Si using a tungsten inert gas (TIG) at different energy input. The effect of energy inputs (1080 and 1350 J/mm) on the melt geometry, topography, microstructure and hardness were examined. The results showed that TIG torch produced melt pools geometry with hemispherical in shape and different geometrical dimensions. Pores were seen to be concentrated at the edges where low melting energies are prominent to entrap escape gases upon fast melt olidification. The melt layers consisted of armed typed dendrites (TiC) and the sizes of dendrites were found to increase with increasing energy input. Microhardness of the surface alloyed layer was increased by 3-4 times compared to CP-Ti.